Malawi Agriculture and Food Security Policy Processes Endline Survey, 2017/18 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Several initiatives in Malawi have sought to strengthen the processes through which the design and content of policies, strategies, and programs in the agriculture sector that affect the nation’s food security are established. A two-part study was done under the New Alliance Policy Acceleration Support: Malawi Project (NAPAS: Malawi) to assess the quality of these policy processes and the institutional framework through which they are conducted and how perceptions of their quality have changed over time. The study is based on a two-round survey of national stakeholders in Malawi on issues centered on agriculture or food security that was conducted in 2015 and 2017/18. This study contains data from the baseline survey. The baseline survey was administered between June and August 2015 to a purposively selected survey sample made of about 100 national level stakeholders in these policy processes. These individuals were asked to complete an online questionnaire that captured their opinions on a range of questions related to the quality of agriculture and food security policy processes at the national level in Malawi. At the end of the baseline survey administration period, responses had been obtained from 86 individuals. The baseline survey consists of five modules: 1)Respondent details; influence of institution within policy processes; 2)Opinion on quality of agriculture and food security policy processes in Malawi; 3) Opinion on quality of institutional architecture for agriculture and food security policy processes in Malawi; 4) Factors that affect agenda-setting within policy processes on agriculture and food security issues and the design of the policies or programs considered; 5)Participation by respondent in agriculture and food security policy process events.